Increased Cell Proliferation in Chronic Helicobacter pylori Positive Gastritis and Gastric Carcinoma – Correlation between Immuno-Histochemistry and Tv Image Cytometry - Erika Szaleczky; László Prónai; Béla Molnár; Lajos Berczi; János Fehér; Zsolt Tulassay (Analytical Cellular Pathology)
Backgound: Epithelial cell proliferation activity has been reported both to be unaltered and increased in Helicobacter pylori (H. pylori) associated chronic gastritis. The proliferation rate decreased following H. pylori eradication, but results are controversial whether this change is dependent on the success of eradication. We compared the cell proliferation activity of H. pylori positive and negative gastric epithelial biopsies in chronic gastritis with and without intestinal metaplasia (IM) and gastric cancer by the expression of proliferation cell nuclear antigen (PCNA) and Tv image cytometry, and assessed the effect of H. pylori eradication on the cell proliferation rate in the gastric epithelium.